Numerical Simulation of Sedimentation Patterns at the Tallo River Estuary (Case Study of New Makassar Container Terminal 2) - Umar, Hasdinar; Rahman, Sabaruddin; Tuharea, Natasha Dewanti (Department of Naval Architecture - Diponegoro University, 2025)
The increase in community activities in the Makassar waters has made the government plan long-term development by exploiting the potential of the sea through coastal reclamation, which aims to meet increasingly limited land needs, one of which is the construction of the New Makassar Container Terminal 2. This development causes changes in coastal sedimentation patterns and current patterns. This research aims to determine the flow patterns and sediment patterns that occur in the Tallo River Estuary due to the construction of the New Makassar 2 Container Terminal and simulated with a numerical hydrodynamic model using scenarios resulting from tidal measurements and wind as generators. The research results show that the flow pattern around the Tallo River Estuary before and after the construction of the New Makassar 2 Container Terminal decreased by 51.288% from 0.105 m/s to 0.051 m/s. The direction of the current at the highest tide conditions moves from the open sea towards the estuary, while at the lowest low tide conditions, it moves from the estuary towards the open sea. The distribution of sediment in the waters of the Tallo River Estuary shows that changes in the basic morphology of the Tallo River Estuary tend to be high; namely, in the review lines 1 - 5, there is a change in sedimentation of 0.055 m; 0.096m; 0.048m; 0.158 m and 0.059 m. So, it can be concluded that the construction of the New Makassar 2 Container Terminal affects the water conditions in the Tallo River Estuary.